Hard work never hurt anyone--or did it? A review of occupational associations with soft tissue musculoskeletal disorders of the neck and upper limb. - Walker-Bone, K; Cooper, C (2005)
Pain in the neck and upper limb is common and contributes greatly to absence due to sickness. Evidence is accumulating that factors such as prolonged abnormal posture and repetition contribute to these conditions. Psychosocial factors may also play a part and the relative importance of these is not yet known. Primary and secondary prevention trials are needed.